Alterações químicas e biológicas do solo e crescimento do milho decorrentes da adição de lodo anaeróbio da estação de tratamento de efluentes da parboilização do arroz. - Vieira, Giulia D'avila (2008)
The rice parbolization process enlarges the physical and nourishing qualities of the grain, creating an effluent rich in organic material and nutrients such as nitrogen and phosphorus. This material called sludge from parbolization can be a source of nutrients to the soil and it can be utilized as a natural fertilizer in the growing of the plants. Considering the importance of a suitable grouping and the best utilization of the organic disposal generated in the agro industry, this work s aim was to evaluate chemical and biological alterations of the soil and the growing of corn plants after the application of anaerobic sludge from the wastewater treatment of rice parboilization. Two experiments were realized. The former in polyethylene greenhouse through the cultivation of corn in vases, containing Ulttissol plus the following doses of an anaerobic sludge obtained from the rice parboilization: 2,15; 4,31; 8,62; 12,93 e 17,24g Kg-1. In this stage, the dry matter s weight of the aerial part, pH, electrical conductivity, total nitrogen, mineral nitrogen P, K and Na of the soil, concentration and total amount accumulated of N, P, K, Ca and Mg in the aerial part of the plants and also the microbial biomass of the ground were evaluated. The latter was developed in the laboratory making use of respirometric vases with the same soil and treatments of the previous experiment seeking the measurement of the microbial activity through the basal respiration of the ground. The application of anaerobic sludge from the rice parbolization enlarged the yield of the corn dry matter, considering that the sludge first dose correspondent to 25% of N supriment for the culture was enough to proportionate an yield more superior than the NPK + lime treatment. The application of anaerobic sludge to the soil increases the pH, electric conductivity, organic carbon contents, N, P, K and Na, if compared to the treatments NPK + lime and control and decreased the mineral nitrogen contents (ammonium NH4 + and nitrate NO3 -) of the ground. The application of sludge from parbolization increased the N, P and K contents and decreased the Ca and Mg contents from the aerial part of the corn, if compared to the treatment NPK + lime and control. The soil microbial activity, measured by the liberation of C-CO2 and the microbial biomass evaluated by the carbon and nitrogen contents, increased with the doses of anaerobic sludge and proportionated decrease in the soil metabolic quotient. The application of sludge did not modify the relations total organic carbon/total organic nitrogen, microbial carbon/ microbial nitrogen, microbial carbon/total organic carbon and microbial nitrogen / total organic nitrogen in relation to the treatment NPK + lime.